Preparation, Characterization and Dielectric Properties of Alginate-Based Composite Films Containing Lithium Silver Oxide Nanoparticles - Giriyappa Thimmaiah, Padma; Mudinepalli, Venkata Ramana; Thota, Subba Rao; Obireddy, Sreekanth Reddy; Lai, Wing-Fu (Frontiers in Chemistry, 2022)
Polymer composites have found applications in diverse areas, ranging from the manufacturing of portable electronic devices to the fabrication of bioactive agent carriers. This article reports the preparation of composite films consisting of sodium alginate (SA) and lithium silver oxide (LAO) nanoparticles. The films are generated by solution casting; whereas the nanoparticles are fabricated by using the hydrothermal method. The effects of the nanoparticles on the morphological, thermal, and dielectric properties of the films are examined by using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) analysis, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). Electrical measurements are also performed to determine the dielectric constant (ε′), dielectric loss (ε″), AC conductivity (σac), electrical moduli (M′ and M″), and impedance (Z' and Z″). The composite films are shown to be crystalline in nature, with nanoparticles having a diameter of 30–45 nm effectively disseminated in the polymer matrix. They also display good dielectric properties. Our results suggest that the films warrant further exploration for possible use in microelectronic applications.